Descriptive Evidence on Labor Market Transitions and the Wage Structure in Germany - Bernd Fitzenberger; Alfred Garloff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Equilibrium search theory suggests that the wage distribution in a cross section of workers is closely related to labor market transitions and associated wage changes. Accordingly, job?to?job transitions are central in explaining the wage distribution. This paper uses the IAB employment subsample to describe the empirics of labor market transitions and the wage structure in Germany. Motivated by search theory, we use the data to explore descriptively labor market transitions and features of the wage structure. We find that labor market transition rates vary substantially over the business cycle and with individual characteristics. Regarding job?to?job transitions, we find considerable wage changes. Most job changes involve considerable gains, but a number of individuals incurs a remarkable loss. Regarding the wage structure, we find strong effects of job?to?job transitions, age, and education on wage mobility. Based on our descriptive analysis, we conclude that indeed a close relationship exists between wages and labor market transitions as predicted by search theory. However, the noticeable share of wage losses following job?to?job changes contradicts a simple search theoretic perspective.
Keywords: J31; J21; E24; J64; 330; search friction; labor market transitions; wages; Arbeitsmarkt; Arbeitsuche; Arbeitsmobilität; Lohnstruktur; Schätzung; Deutschland